The scope of ‘de novo’ review of an arbitral tribunal’s jurisdiction - CHAN, Darius (Institutional Knowledge at Singapore Management University, 2015)
In PT First Media TBK (formerly known as PT Broadband Multimedia TBK) v Astro Nusantara International BV [2014] 1 SLR 372 (“Astro”), the Singapore Court of Appeal held that the Court will apply a de novo standard of review when reviewing an arbitral award on the grounds of lack of jurisdiction. What exactly is the scope of de novo review? Specifically, can a party adduce before the Court fresh evidence that had not been put before the arbitral tribunal? Can a party insist that the Court re-hear oral testimony of witnesses who had testified before the arbitral tribunal?These separate but related issues can arise at two different stages. One, when a party refers a tribunal’s ruling on jurisdiction for curial review under s 10 of the International Arbitration Act (“IAA”), and two, when a party challenges a tribunal’s jurisdiction when setting aside or resisting enforcement of the tribunal’s award under the IAA read with the Model Law. Two recent Singapore High Court judgments considered these issues. In Government of the Lao People’s Democratic Republic v Sanum Investments Ltd [2015] SGHC 15 (“Sanum”), and AQZ v ARA [2015] SGHC 49 (“AQZ”), which were delivered approximately three weeks apart, the Singapore High Court appeared to give somewhat differing guidance.This note discusses the apparently conflicting positions, and suggests a path for navigation should the same issue confront the Singapore Courts again.